PENGARUH INKLUSI KEUANGAN DAN PERTUMBUHAN EKONOMI TERHADAP RISIKO KREDIT PERBANKAN - Parsa, Silviani Ade Damayanti; Sedana, Ida Bagus Panji; Dana, I Made; Dewi, I Gusti Ayu manuati (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.06.TAHUN.2023DO - 10.24843/EEB.2023.v12.i06.p08, 2023)
The COVID-19 pandemic has caused the economy to decline and activities in various sectors in Indonesia, including the banking sector, have been hampered, resulting in higher bank credit risk. The purpose of this study is to analyze the effect of financial inclusion and economic growth on bank credit risk. This study uses secondary data that is accessed on the official website of the national banking institution, the national statistical agencys, the website of the bank concerned. The population in this study are banks in the category of Commercial Banks Business Group 3 registered with the OJK during the 2016 - 2020 period with a total sample of 10 banks which were taken using the purposive sampling method. The analysis technique used is multiple linear regression analysis. The results showed that financial inclusion and economic growth had a significant negative effect on bank credit risk. Increased financial inclusion causes the risk of bank credit to decrease and increased economic growth indicates the level of public welfare is also increasing so that it is able to minimize the existence of non-performing loans.